Autonomic Modulation of Cardiac Activity Across Levels of Sleep Depth in Individuals With Depression and Sleep Complaints. Issue 2 (February 2020) - Saad, Mysa; Ray, Laura B.; Bradley-Garcia, Meenakshie; Palamarchuk, Iryna S.; Gholamrezaei, Ali; Douglass, Alan; Lee, Elliott K.; Soucy, Louis; Robillard, Rebecca
ABSTRACT: Objective: We assessed mean heart rate (HR) and HR variability (HRV) across wake, rapid eye movement (REM) sleep, and non-REM (NREM) sleep, and across varying levels of NREM sleep depth in individuals with depression and sleep complaints. Methods: Retrospective polysomnographic data were obtained for 25 individuals diagnosed as having depression (84% female; mean age = 33.8 ± 12.2 years) and 31 mentally healthy controls (58.1% female; mean age = 37.2 ± 12.4 years). All were free of psychotropic and cardiovascular medication, cardiovascular disease, and sleep-related breathing disorders. HR and time-domain HRV parameters were computed on 30-second electrocardiography segments and averaged across the night for each stage of sleep and wake. Results: Compared with the control group, the depression group had higher HR across wake, REM, and all levels of NREM depth ( F (1, 51) = 6.3, p = .015). Significant group by sleep stage interactions were found for HRV parameters: SD of normal-to-normal intervals (SDNN; F (2.1, 107.7) = 4.4, p = .014) and root mean square differences of successive R-R intervals (RMSSD; F (2.2, 113.5) = 3.2, p = .041). No significant group difference was found for SDNN or RMSSD during wake (all, p ≥ .32). However, compared with the control group, the depression group had significantly lower SDNN in REM ( p = .040) and all NREM stages (all p ⩽ .045), and lower RMSSD during NREM 2 ( p = .033) and NREM 3 ( p = .034). Conclusions: This study suggests that the abnormalities in autonomic cardiac regulation associated with depression and sleep problems are more prominent during sleep, especially NREM sleep, than during wake. This may be due to abnormalities in parasympathetic modulation of cardiac activity.